2007
DOI: 10.1080/18811248.2007.9711329
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Total Amounts of Anthropogenic Radionuclides in the Japan Sea

Abstract: We estimated the total amounts of anthropogenic radionuclides, consisting of 90 Sr, 137 Cs, and 239þ240 Pu, in the Japan Sea for the first time based on experimental data on their concentrations in seawater and seabed sediment. The radionuclide inventories in seawater and seabed sediment at each sampling site varied depending on the water depth, with total inventories for 90 Sr, 137 Cs, and 239þ240 Pu in the range of 0.52-2.8 kBq m À2 , 0.64-4.1 kBq m À2 , and 27-122 Bq m À2 , respectively. Based on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The inventories of 239þ240 Pu in the sediments of PA-11 (3.75 AE 0.29 Bq/m 2 ) and PA-1 (1.38 AE 0.06 Bq/m 2 ) . These values were significantly lower than those of the most marginal seas: 16e80 Bq/m 2 in the East China Sea (Nagaya and Nakamura, 1992), 10e12 Bq/m 2 in the Yellow Sea and 13e68 Bq/m 2 , 27e122 Bq/m 2 (Ito et al, 2007), 5.7e241 Bq/m 2 (Zheng and Yamada, 2005) in the Japan Sea/East Sea, and 0.6e74 Bq/m 2 in the Sea of Okhotsk. The above results agreed well with previous findings that the inventories of 239þ240 Pu in the sediment were inversely related to water depth and linearly correlated with sediment accumulation rates , which also meant the inventories of radionuclides in sediments in the shallow water marginal seas and areas which have a relatively small volume of seawater above or have a high sediment accumulation rate were general higher than those of the deep-seas.…”
Section: Distribution Of 239þ240 Pu In Sedimentscontrasting
confidence: 59%
See 1 more Smart Citation
“…The inventories of 239þ240 Pu in the sediments of PA-11 (3.75 AE 0.29 Bq/m 2 ) and PA-1 (1.38 AE 0.06 Bq/m 2 ) . These values were significantly lower than those of the most marginal seas: 16e80 Bq/m 2 in the East China Sea (Nagaya and Nakamura, 1992), 10e12 Bq/m 2 in the Yellow Sea and 13e68 Bq/m 2 , 27e122 Bq/m 2 (Ito et al, 2007), 5.7e241 Bq/m 2 (Zheng and Yamada, 2005) in the Japan Sea/East Sea, and 0.6e74 Bq/m 2 in the Sea of Okhotsk. The above results agreed well with previous findings that the inventories of 239þ240 Pu in the sediment were inversely related to water depth and linearly correlated with sediment accumulation rates , which also meant the inventories of radionuclides in sediments in the shallow water marginal seas and areas which have a relatively small volume of seawater above or have a high sediment accumulation rate were general higher than those of the deep-seas.…”
Section: Distribution Of 239þ240 Pu In Sedimentscontrasting
confidence: 59%
“…Therefore, inventories of radionuclides in sediments in the shallow water marginal seas and areas which have a relatively small volume of seawater above or have a high sediment accumulation rate were general higher than those of the deep-seas (Duran et al, 2004;Hirose, 2009;Moon et al, 2003;WOMARS, 2005). The distributions of Pu isotopes in sediments of marginal seas of the western North Pacific have been intensively studied in the late half of the last century Hong et al, 2002;Ito et al, 2007;Kim et al, 2002Kim et al, , 2004Lee et al, 2003;Nakamura, 1987, 1992;Wang and Yamada, 2005;Yamada et al, 1996). Many studies have also demonstrated that the 240 Pu/ 239 Pu atom ratio is a powerful tool to verify the sources of Pu contamination in the marine environment.…”
Section: Introductionmentioning
confidence: 97%
“…A more comprehensive summarization about the distribution of Pu isotopes in the western North Pacific and its marginal seas in the literature (Buesseler, 1997;Dong et al, 2010;Hong et al, 1999;Ito et al, 2007;Kim et al, 2003;Lee et al, 1998Lee et al, , 2003Lee et al, , 2004Lee et al, , 2005Liu et al, 2011a;Moon et al, 2003;Nagaya and Nakamura, 1992;Oikawa et al, 2011;Otosaka et al, 2006;Pettersson et al, 1999;Wang and Yamada, 2005;Yamamoto et al, 1990;Yamada, 2005, 2006b, c) is given in Table 2. The concentration of 239+240 Pu activity and 240 Pu/ 239 Pu atom ratio in the surface sediments ranged from 0.002 to 5.38 mBq g −1 and from 0.150 to 0.281, respectively, except in the surface sediment collected near the Bikini Atoll, where the high concentration of 12.5 mBq g −1 and high atom ratio of 0.336 have been reported (Buesseler, 1997;Lee et al, 2005).…”
Section: Baseline Data For the Pu Distribution In The Western North Pmentioning
confidence: 99%
“…To compare the distributions of Pu isotopes in the marine sediments before and after the FNDPP accident, the background dataset needs to be established. Due to the potential applications of Pu isotopes as a chemical tracer for oceanic processes and as a source identifier for radioactive contamination, over the past decades, the distribution of Pu isotopes in the western North Pacific and its marginal seas have been studied intensively (Buesseler, 1997;Dong et al, 2010;Hong et al, 1999;Ito et al, 2007;Kim et al, 2003;Lee et al, 1998Lee et al, , 2003Lee et al, , 2004Lee et al, , 2005Lindahl et al, 2011;Liu et al, 2011a;Moon et al, 2003;Nagaya and Nakamura, 1992;Oikawa et al, 2011;Otosaka et al, 2006;Pettersson et al, 1999;Wang and Yamada, 2005;Yamada, 2005, 2006b, c). For the Japanese near-coastal marine environment, especially the estuaries, leaching of contaminated soils is another potential pathway for radioactive contamination in addition to the atmospheric deposition from the accident plume and the direct release of contaminated plant cooling waters (Bailly du Bois et al, 2012).…”
mentioning
confidence: 99%
“…91,92 The shape of the 239,240 Pu activity peak is related to the location of the sea area, for example, the peak for the Japan Sea and the Mediterranean Sea are broad, and the peak observed for the northwestern Pacific Ocean is sharp. [93][94][95] It was estimated that the residence time of 239,240 Pu in the subsurface layer is 400-600 years and thus the 239,240 Pu stored in the subsurface layer could serve as an important Pu source in adjacent s eas. 2…”
Section: Distribution Of Pu In the Marine Environmentmentioning
confidence: 99%